DIMORFISMO SEXUAL SECUNDÁRIO EM MORCEGOS: EXPLORANDO A HIPÓTESE DA “BIG MOTHER” - MARCHIORO, SABRINA (2017)
The secondary sexual dimorphism may be shown in several manners, and one of the most common is the sexual dimorphism in size. In bats, this dimorphism tends towards the females. The "Big Mother" hipothesys says that bigger females can alocate a larger amount of resources in reproduction, and an unfolding of this hipothesys is that females could have relatively larger wings than males in the sense of carrying the extra weight of pregnancy and newborn pup. So the objectives of this chapter were to test if the females are globally bigger and/or if they posess wings relatively bigger than males. Eight morphometrical linear mesures were taken from nine neotropical bat species belonging to three families. The absolute secondary sexual dimorphism in each species was tested with Student's t with the variable of length of head/body to each species. To test de the relative secondary sexual dimorphism a principal components analisys (PCA) was made and the result of the scores of the two first PCs were used to make tests Hotelling's T² and also discriminant analisys to each of the nine species. Only four species had females bigger in absolute size: Sturnira lilium, Artibeus lituratus, Myotis izecksohni and Eptesicus furinalis, while Molossus molossus was the only species with males bigger than females. The remaining species didn't show differences in the absolute size among the sexes. As for the relative dimorphism, all nine species showed relative differences among the sexes, with females of eight species having (relatively) larger wings than males, with exception of Molossus rufus. So, the present work corroborates with the "Big Mother" hipothesys, because even when females were smaller than males globally, or there was no difference among the sexes in absolute size, in a general manner females were larger than males in the relative size of wing elements. This allows good aerodynamics, maneuverability, stability, propulsion and sustentaining during flight, important characteristics for carrying the extra weight of the pup.